Pharmacokinetic Parameters and Tissue Withdrawal Intervals for Sheep Administered Multiple Oral Doses of Meloxicam - Sarah Depenbrock; Tara Urbano; Jessie Ziegler; Scott Wetzlich; Maaike O. Clapham; Lisa A. Tell (Animals, 2021)
Meloxicam is an anti-inflammatory drug used to treat pain and inflammation in ruminants including sheep, and pharmacokinetic studies are needed to protect the food supply from drug residues after use in food-producing animals. This study estimated plasma pharmacokinetic parameters and meat withdrawal intervals (WDI) for market sheep after multiple daily oral doses of meloxicam. Single and multiple dose plasma pharmacokinetic studies, a multi-dose tissue depletion study, and a follow-up study to investigate if events prior to slaughter were associated with differences in plasma meloxicam concentrations, all using sample data collected after completion of dosing, were completed. Using regulatory agency methods for calculating withdrawal times, an estimated WDI of at least 10 d following the last dose is recommended for market lambs treated with 10 daily oral 1 mg/kg doses of meloxicam tablets suspended in water. The effect of events surrounding slaughter on plasma meloxicam concentrations in lambs is unknown but should be considered if plasma samples are obtained immediately prior to or during the slaughter process and used for pharmacokinetic investigations.